Pengaruh Profitabilitas, Likuiditas, Solvabilitas dan Ukuran Perusahaan terhadap Nilai Perusahaan - Debora Magdalena Sundayana; Yovita Ariani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Investment in Indonesia decreased by 1.94 percent from 2019 to 2020. The decline in investment demand makes (assuming a fixed supply) stock prices decline which also has an impact on company value. Firm value is an important factor for investors before making an investment because firm value reflects the amount of return from the company to investors. This study aims to analyze the effect of profitability proxied by ROA and GPM, liquidity proxied by CR, solvency proxied by DER and company size on firm value using IBM SPSS Statistic 26.0 for Windows software. In this study, data were collected from all Food and Beverage sub-sector companies listed on the IDX from 2020 to 2022 by taking into account the completeness of the data during the study period. The purposive sampling techique was applied to obtain 24 companies as research sample. This study uses multiple regression as data analysis method carried out by the coefficient of determination test and hypothesis testing. The result showed that profitability proxied by ROA affects firm value with a significance level of 0.006. However, profitability proxied by GPM, liquidity proxied by CR, solvency proxied by DER and company size have no effect on firm value.